Building trusting relationships in teams to support evidence use and implementation in human services: feasibility and acceptability of a training and coaching approach - Metz, Allison; Jensen, Todd M.; Dicharry, Lacy; Farley, Amanda B. (Frontiers in Health Services, 2024)
BackgroundProfessionals who provide implementation support in human service systems describe relationships as being critical to support evidence use; however, developing trusting relationships are not strongly featured in implementation science literature. The aims of this study were to (a) assess the feasibility and acceptability of a theory-driven training and coaching approach for building trusting relationships among members of an implementation team who were supporting the implementation of an evidence-informed program in a public child welfare system in the United States and (b) gauge the initial efficacy of the approach in terms of the development of trusting relationships and subsequent implementation outcomes.MethodsConsistent with a convergent mixed-methods approach, we collected both quantitative and qualitative data to address our research questions. Quantitative methods included an adapted version of the Trusting Relationship Questionnaire, a seven-item measure of psychological safety, and items designed to measure acceptability of the training. Qualitative data were collected through semi-structured interviews with participants.ResultsSixteen individuals participated in the program, consisting of a kick-off training event, five monthly training modules, and five monthly coaching sessions with implementation team leads. Session attendance rates and self-reported satisfaction highlight the general feasibility and acceptability of the training and coaching approach. On average, participants also reported significant increases over time in their perceptions that they were trusted by their team. Results from in-depth interviews further indicated the efficacy of the program in terms of cultivating trust among team members and promoting several elements that were theorized to link trusting relationships to implementation outcomes.DiscussionFindings suggest the training and coaching approach for trust building was acceptable and feasible. Additionally, results indicate the value of the approach in building trust among implementation partners to increase commitment to implementation efforts, promote a culture of learning and psychological safety, and increase participants' sense of capability and motivation for supporting implementation.